Reciprocity, self-interest and reputation: debt vs equity contracts - Shah, Syed Munawar (Islamic economic studies, 2019)
Purpose The purpose of this paper is to examine whether reputation element affects the decision relative performance of trust, bonus and incentive contracts using social laboratory experiments. Design/methodology/approach The study conducts the following lab experiments bonus-incentive treatment without reputation, bonus-incentive treatment with reputation and trust-incentive treatment with reputation. Findings The study finds that the reputation and fairness concerns, in contrast to self-interest, may have a decisive impact on the actual and optimal choices in the reciprocity-based contracts. The principal pays higher salaries in the bonus contract as compared to an incentive contract. Originality/value The study contributes to the behavioral economic literature in the following dimensions. The existing literature on lab experiments considers a bonus contract as better than the debt contract; however, it does not consider the trust contract better than the debt contract.